The Effect of Testosterone Hormone and Age on Muscle Development of Kacang Doe - Rudiono, D (ANIMAL PRODUCTION, 2007)
A total of 40 Kacang does with average initial body weight (BW) of 10.2 kg were used in factorial experiment (4x2) based on completely randomized design (CRD) to determine muscle development. The first factor was the doses of testosterone consisted of four levels, i.e.: control (t0);  0.77 (t1);  1.54 (t2); and 2.31 (t3) mg/kg BW.  The second factor was the age of does, i.e.: 7-8 month (u1) and  9-12 month (u2).  So that there were eight combinations of treatments, each was replicated five times.  Animals in treatment group were injected with testosterone propionate (TP) weekly for 90 days. They were fed on ration to gain 50 g/day. Variables observed were the number of fibril in longissimus dorsi and rectus femoris (pc/100m), the weight of longissimus dorsi and rectus femoris muscles, and Loin Eye Area (cm2). There was significant interaction between doses and age on the fibril number of longissimus dorsi and rectus femoris muscle, and also Loin Eye Area.  The best result was showed by the combination treatment of t1 andu1. Testosterone propionate injection did not significantly affect the weight of longissimus dorsi and rectus femoris muscles. Meanwhile, age significantly influenced weight of longissimus dorsi muscle only. In conclusion, injection of 0.77 mg/kg BW/day TP to does with 7-8 month of age showed the best result on muscle mass. (Animal Production 9(2): 59-66 (2007)Key Words : Kacang doe, testosterone hormone, chronological age, muscle development